Hydrologic connectivity and land cover affect floodplain lake water quality, fish abundance, and fish diversity in floodplain lakes of the Wabash‐White River basin. (10th November 2021) - Carlson Mazur, Martha L.; Smith, Bradley; Bird, Broxton; McMillan, Sara; Pyron, Mark; Hauswald, Cassie
Abstract: Floodplain lakes are important aquatic resources for supporting ecosystem services, such as organismal habitat, biodiversity, and the retention of nutrients and sediment. Due to geomorphic alteration of river channels and land‐cover change, degradation to floodplain lakes in the Ohio River basin is occurring at a rate that will escalate as climate change causes increased flood intensity and the seasonal redistribution of rainfall. A better understanding of the local drivers that affect oxbow lakes is needed for targeted floodplain restoration efforts designed to slow degradation. We examined the effects of land cover, topography, and hydrologic connectivity on water quality and fish diversity and abundance in nine floodplain lakes with potentially high remnant ecological function in the Wabash‐White watershed (Indiana, Ohio, and Illinois). Data collection included water‐quality parameters; stable water isotopes; total phosphorus, total nitrogen, and chlorophyll‐ a ; and fish community diversity and abundance. Results indicate that hay/pasture land cover and decreased topographic relief in the local oxbow watersheds, along with reduced river hydrologic connectivity, were related to an increase in total phosphorus, total nitrogen, and chlorophyll‐ a . Greater biodiversity and abundance in fish assemblages were evident in oxbow lakes that were more disconnected from the main channel. The results of this study suggest that hydrologic connectivity of oxbow lakes with the contributing drainage area and the main channel influence nutrients and fish communities. Knowing the influencing factors can help ecosystem managers better protect these valuable floodplain lake ecosystems and prioritize restoration efforts amidst increasing stressors due to climate and land‐use changes.